2012
DOI: 10.1021/om3010993
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects in Lanthanide Sandwich Complexes Containing Bulky Cyclooctatetraenyl Ligands

Abstract: This paper gives a full account of the complex reaction system LnCl3/(COT″)2– (COT″ = 1,4-bis(trimethylsilyl)cyclooctatetraenyl dianion). Four different series of organolanthanide complexes of this bulky COT ligand have been reported: (1) anionic sandwich complexes containing [Ln(COT″)2]− anions, (2) dimeric chloro-bridged mono(COT″) complexes, (3) cluster-centered multidecker-sandwich complexes, and (4) linear triple-decker sandwich complexes. In order to get a more complete picture of the reaction system LnC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 56 publications
(67 reference statements)
3
43
0
Order By: Relevance
“…These anionic species are interesting precursors as they can undergo clean redox reactions with anhydrous CoCl 2 with the formation of the linear, homoleptic triple‐decker sandwich complexes [Ln 2 (COT′′) 3 ]. Thus far, binuclear [Ln 2 (COT′′) 3 ] complexes have been reported for Ln = Nd, Gd, Dy, Ho, and Er . Single‐ion magnet (SIM) or SMM behavior has been reported for various Ln(COT′′) compounds of these types, including, for example, [Li(THF)(DME)][Dy(COT′′) 2 ], [Li(DME) 3 ][Nd(COT′′) 2 ], [Li(DME) 3 ][Dy(COT′′) 2 ], [Ln 2 (COT′′) 3 ] (Ln = Gd, Dy), [Er 2 (COT′′) 3 ], and [Cp*Ln(COT)] (Ln = Dy, Ho, Er; Cp* = η 5 ‐pentamethylcyclopentadienyl) .…”
Section: Introductionmentioning
confidence: 99%
“…These anionic species are interesting precursors as they can undergo clean redox reactions with anhydrous CoCl 2 with the formation of the linear, homoleptic triple‐decker sandwich complexes [Ln 2 (COT′′) 3 ]. Thus far, binuclear [Ln 2 (COT′′) 3 ] complexes have been reported for Ln = Nd, Gd, Dy, Ho, and Er . Single‐ion magnet (SIM) or SMM behavior has been reported for various Ln(COT′′) compounds of these types, including, for example, [Li(THF)(DME)][Dy(COT′′) 2 ], [Li(DME) 3 ][Nd(COT′′) 2 ], [Li(DME) 3 ][Dy(COT′′) 2 ], [Ln 2 (COT′′) 3 ] (Ln = Gd, Dy), [Er 2 (COT′′) 3 ], and [Cp*Ln(COT)] (Ln = Dy, Ho, Er; Cp* = η 5 ‐pentamethylcyclopentadienyl) .…”
Section: Introductionmentioning
confidence: 99%
“…Uranocene is unreactive to lithiation, 9 and all reported trivalent uranocene-type complexes have been prepared via reduction of [U IV (COT-R) 2 ] (R = CH 3 , 10 13 Single crystals of 3 were grown in a concentrated solution of a 50:50 mixture of DME/hexanes. Complex 1 crystallizes in the triclinic P1̅ space group where the U III ion is bound to two COT″ ligands in a η 8 -fashion to form a distorted sandwich complex.…”
mentioning
confidence: 99%
“…In this compound the bulky COT leads to coordination of only one THF per Ln in comparison to the long-known parent chloro-bridged dimers [(COT)Ln(-Cl)(THF) 2 ] 2 [87].…”
Section: Lanthanide Cyclooctatetraenyl Complexesmentioning
confidence: 98%
“…It was found that the steric effect of either COT or COT TBS on the molecular structures of the anionic sandwich complexes with coplanar ring ligands is rather small. In (COT )Yb(DippForm)(THF), the combination of COT with a sterically demanding formamidinate ligand in the coordination sphere of Yb 3+ still leaves room for THF coordination [87].…”
Section: Lanthanide Cyclooctatetraenyl Complexesmentioning
confidence: 99%
See 1 more Smart Citation